Pengembangan Kemasan Inovatif Susu Kambing Bumdes Desa Lalang Sembawa untuk Meningkatkan Nilai Jual Produk Lokal: Pengabdian - Rike Rahayu; Eka Putri Dwitami; Nandhita Salzabilla; Vegita Julianda; Susi Hildayanti; Emilda; Muhammad Wadud (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Community-Owned Enterprises (BUMDes) in Desa Lalang Sembawa face challenges in marketing and digitalization, limiting the potential of local goat milk products. This study aims to develop innovative packaging and digital marketing strategies to increase product value and market reach. The research uses a qualitative community service approach with direct mentoring to empower goat milk UMKM actors. The population includes all BUMDes managers of